Kajian Hukum Pencurian dengan Kekerasan - Harianto Harianto; Muhammad Natsir; Muhammad Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This research was conducted with the aim of identifying and analyzing the factors causing the occurrence of the criminal act of theft with violence, as well as finding out and analyze the application of the law on the crime of theft with violence (Case Study Decision No.147/Pid.B/2020/PN.Pinrang). This research uses normative and empirical research. The cause of the crime of theft with violence There are two underlying factors, namely the education factor, and the parent's income factor. The application of the law to the crime of theft with violence committed by children in the Case Study Decision No. 147/Pid.B/2020/PN.Pinrang starting from the position of the case, the indictment of the public prosecutor, the demands of the public prosecution, and the judge's decision so that Cakra Bin Hasan was rightly proven guilty of committing the crime of theft accompanied by violence, and the decision was good at the formal point of view and the material is in accordance with the applicable provisions.